2013
DOI: 10.1016/j.bpj.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous versus Slowed-Down Brownian Diffusion in the Ligand-Binding Equilibrium

Abstract: Measurements of protein motion in living cells and membranes consistently report transient anomalous diffusion (subdiffusion) that converges back to a Brownian motion with reduced diffusion coefficient at long times after the anomalous diffusion regime. Therefore, slowed-down Brownian motion could be considered the macroscopic limit of transient anomalous diffusion. On the other hand, membranes are also heterogeneous media in which Brownian motion may be locally slowed down due to variations in lipid compositi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
(66 reference statements)
2
45
1
Order By: Relevance
“…In terms of mean-squared displacement 〈 R 2 〉, NHB thus preserves the long-time behavior of NHC, but does not feature the initial anomalous transient. In a previous work (Soula et al, 2013), we showed that decreasing the ratio of diffusion coefficients D in / D out in NHB, leads to accumulation at equilibrium inside the patch. We obtained a very good theoretical approximation of this accumulation with a simple expression: Nin/NT=ϕϕ+(1ϕ)DinDout…”
Section: Resultsmentioning
confidence: 62%
“…In terms of mean-squared displacement 〈 R 2 〉, NHB thus preserves the long-time behavior of NHC, but does not feature the initial anomalous transient. In a previous work (Soula et al, 2013), we showed that decreasing the ratio of diffusion coefficients D in / D out in NHB, leads to accumulation at equilibrium inside the patch. We obtained a very good theoretical approximation of this accumulation with a simple expression: Nin/NT=ϕϕ+(1ϕ)DinDout…”
Section: Resultsmentioning
confidence: 62%
“…This setup reduces the diffusional mobility of R and G by a factor of 2 more strongly than in the free-diffusion case (to 0.26D 0 ), a behavior that has already been suggested in theoretical studies (61). If the single R Ã is considered to be not part of a rack, the encounter rate between R Ã and G is increased due to confinement compared to the free-diffusion case (also compare to Soula et al (71)). This increase is compensated by the decreased long-range diffusion through racks.…”
Section: Resultsmentioning
confidence: 82%
“…It has been shown that obstacles can increase educt encounter rates (71). In our case, the R Ã G encounter rate FIGURE 5 Microscopic ReaDDy simulation of the pre-complex scenario.…”
Section: Existence Of Racks Of Rhodopsin Dimersmentioning
confidence: 95%
See 1 more Smart Citation
“…Let us mention a few recent publications concerning the applications of subdiffusive fractional equations. The work in [3] studied the applications to the transport in biological cells. The work in [6,7] studied the fractional chemotaxis diffusion equation.…”
Section: Introductionmentioning
confidence: 99%